Analisis Tindak Tutur AsertifIklan Elektronik Telepon Genggam Di Berniaga.ComEdisi Februari 2014 - Budi Utomo, Mohamat (2016)
This study has two objectives: 1) Describe the form of speech acts assertive electronic advertising in the mobile phone edition berniaga.com February 2014. 2) describe the factors behind the occurrence of speech acts assertive electronic advertising berniaga.com mobile phone in February 2014 edition. This research uses qualitative descriptive. This study used a qualitative descriptive because the data collected in the form of words, pictures, and not numbers. data collection techniques used in this study are engineering and technical refer note. Techniques and techniques see note means that researchers as a key instrument do penyimakan careful, focused and careful review of the primary data source. Based on data from this study concluded that 1) there are three types of speech acts assertive electronic advertising berniaga.com mobile phone in February 2014 edition. Of speech acts assertive used include a) the form of assertive suggest, b) suggest assertive form, c) the form of assertive claim. 2) there are eleven kinds of things that the background occurrence of speech acts assertive electronics ad mobile phone in berniaga.com edition of February 2014. The following factors were behind the assertive speech acts include a) by selling mobile phone in speaker, b) based on the condition of the mobile phone c) based on residence speakers, d) based on the system used cell phones, e) based on the telephone number that the speaker, f) based on the price of the desired speaker, g) based on the specifications of the handset, h) based on the completeness of mobile phones, i) based mobile phone warranty is still valid, j) based on the exact price of the speakers, and k) based on the economic circumstances of speakers. Keywords: speech acts, assertive